GULF COOPERATION COUNCIL (GCC) CRISIS: SAUDI ARABIA'S SEVERING OF DIPLOMATIC RELATIONS WITH QATAR AND THE IMPACT ON THE MIDDLE EAST - 'Nisa, Sayyidah Ilman (Jurusan Ilmu Hubungan Internasional, 2024)
The purpose of this research is to find out the factors and reasons for Saudi Arabia to sever diplomatic relations with Qatar. This research uses a type of descriptive qualitative research that examines the substance and observation of phenomena and focuses on the process and the meaning of the results. Supported by literature studies from several literature books, journals, and electronic media. The results of this study indicate the policy of Saudi Arabia and the Arab Quartet countries to carry out a diplomatic break with Qatar against the background of Saudi Arabia's interests to maintain Saudi Arabia's security stability, the unity of the Gulf Countries (GCC), and the Middle East region and maintain the status quo of Saudi Arabia. in the Middle East. The blockade carried out by Saudi Arabia against Qatar has connectivity with each other related to Qatar's foreign policy which is quite contrary to the agreement of the Gulf Countries (GCC) and Saudi Arabia's national interests, then Saudi Arabia's balance of power with hegemony over Qatar as an effort to maintain stability security with Saudi Arabia's dominant position by giving ultimatum demands as a way of Saudi Arabia's coercive diplomacy towards Qatar for a certain period of time.